Violence against Women: Challenges in Fulfilling the 2030 Agenda for Sustainable Development and the Implementation of the 2011 Istanbul Convention in the Republic of Croatia - Fabijanić Gagro, Sandra; Škorić, Marissabell (Pécs journal of international and European law, 2024)
Year 2024 marks the tenth anniversary of the entry into force of the Istanbul Convention on preventing and combating violence against women and domestic violence. At the same time, the world has just passed the halfway point in the implementation of the Sustainable Development Goals (SDGs), which are enshrined in the 2030 Agenda for Sustainable Development. By comparing the results of both instruments, this paper aims to highlight current trends in universal and national efforts to combat violence against women. Based on the premise that violence against women, is unfortunately, still pervasive and can occur anytime and anywhere, this paper addresses three main topics: 1) the fundamental challenges for strengthening gender equality and women’s empowerment in combating violence against women globally and the current results of the implementation of SDG 5; 2) the contribution of key international documents; and 3) the assessment of the implementation of the 2011 Istanbul Convention in the Republic of Croatia through the comments of the recent GREVIO report.